2011
DOI: 10.1074/jbc.m110.204685
|View full text |Cite
|
Sign up to set email alerts
|

Highly Cooperative Dependence of Sarco/Endoplasmic Reticulum Calcium ATPase (SERCA) 2a Pump Activity on Cytosolic Calcium in Living Cells

Abstract: Sarco/endoplasmic reticulum (SR/ER) Cadynamics. F-L577 will be useful for future studies on Ca 2؉ signaling involving SERCA2a activity. Intracellular Ca2ϩ plays a pivotal role in controlling numerous cellular processes such as exocytosis, gene transcription, cell proliferation, muscle contraction, and cell survival (1). The level of intracellular Ca 2ϩ is determined by the balance between the influx that introduces Ca 2ϩ into the cytoplasm and the efflux that removes it from the cytoplasm. The key molecules in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…Ranolazine also has been shown to indirectly stabilize SERCA in hearts of dogs with mild cardiac failure (18). SERCA plays a dynamic role in controlling cytosolic calcium content (54). Forster resident energy transfer studies of SR luminal calcium with specifically labeled SERCA2a showed that SERCA2a conformational changes directly coincided with calcium pump activity and appearance of luminal SR calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Ranolazine also has been shown to indirectly stabilize SERCA in hearts of dogs with mild cardiac failure (18). SERCA plays a dynamic role in controlling cytosolic calcium content (54). Forster resident energy transfer studies of SR luminal calcium with specifically labeled SERCA2a showed that SERCA2a conformational changes directly coincided with calcium pump activity and appearance of luminal SR calcium.…”
Section: Discussionmentioning
confidence: 99%
“…After stimulation of a cell, the SR is able to replenish its content by pumping calcium via the sarco/endoplasmic reticulum calcium ATPase (SERCA) pumps localized strategically in close apposition to the plasma membrane and the mitochondria (Fig. 2, E and F) (Putney, 1986;Floyd 520 and Wray, 2007;Satoh et al, 2011). Thus, the SR is able to refill its calcium stock from both the extracellular space and the mitochondria.…”
Section: Examples Of Calcium Compartmentalization Involved In Vasculamentioning
confidence: 99%
“…A comparison of the tetracysteine tag with YFP demonstrated that the insertion of the two fluorescent proteins can lead to alterations in pharmacological and signaling properties of the receptor, whereas the use of FlAsH as a FRET acceptor for CFP improved both the sensitivity of detection and the downstream signaling of the receptor (26). Similar tetracysteine-based strategies have been employed to study the activation of 2 -adrenoreceptors (2627), acetylcholine receptors (2829), endothelin receptor (30), Ca-ATPase (3132), and amyloid formation (19). …”
Section: Resultsmentioning
confidence: 99%